Lake and River Restoration Method, Evaluation and Management - Pan, Gang; Song, Lirong; Chen, Qiuwen; Lyu, Tao (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Eutrophication has become one of the major environmental issues of global concern due to the adverse effects on water quality, public health, and ecosystem sustainability. Fundamental research on the restoration of eutrophic freshwaters, i.e., lakes and rivers, is crucial to supporting further evidence-based practical implementations. The 12 published research papers can be classified into to three major aspects of this topic, into which they provide valuable contributions. Firstly, a background investigation into the migration of nutrients and the characteristics of submerged biota will guide and assist understanding of the mechanisms of future restoration. Secondly, various restoration strategies are studied and evaluated, including control of both external and internal nutrient loading. Thirdly, an evaluation of field sites after restoration treatment is reported in order to support the selection of appropriate restoration approaches. We foresee that the papers will significantly contribute to eutrophication control, natural water sustainability, and ecological restoration.